Students’ meaning-making of nature of science: interaction between visual, verbal, and written modes of representation - Cheung, KKC; Oancea, A; Erduran, S (Wiley, 2024)
Students' understanding of nature of science (NOS) has been largely examined primarily in written or verbal modes. The visual, verbal, and written modes are essential for students' meaning-making of NOS. However, research has sidelined the interaction among these three modes in understanding students' collaborative discourse of NOS. Informed by theories of multimodality and social semiotics, this paper investigates the interactions between the visual, verbal, and written modes as groups of students engaged in explicit-reflective multimodal representation during NOS instruction. Utilizing a collective case study approach, we planned NOS instruction with teachers, and videotaped how each focal group of students in two grade seven classes in Hong Kong constructed multimodal representations of NOS. Multimodal discourse analysis revealed that the three modes fulfill various purposes during students' co-construction of multimodal representations of NOS. The interaction between the three modes facilitates meaning-making of NOS in four ways: (a) students' re-semiotization of discursive scientific practices into their multimodal ensembles; (b) bridging students' writing of scientific reports to scientists' social certification and dissemination; (c) connecting students' decontextualized meaning-making to contextualized meaning-making of methods and methodological rules; and (d) facilitating students' embodied semiosis in social organizations and interactions of science. Focusing on four episodes of co-constructing multimodal representations of NOS, we illustrate how students' meaning-making of NOS is multimodal in nature and how various modes have their own affordances. We discuss future research directions on how multimodality can facilitate students' meaning-making of NOS.